A influência do ensino escolar e da cultura árabe-islâmica no aprendizado em saúde dos alunos de três escolas da Tríplice Fronteira - Mansour, Noura Reda (2017)
The triple frontier region is constituted by the alliance of three cities from different countries, being them, Foz do Iguaçu, located in West of Paraná-Brasil; Ciudad Del Este, located in Alto Del Paraná- Paraguai and Puerto Iguazu, located in Argentina. In the city of Foz do Iguaçu – PR are located two schools of arab origin and muslim religion which live in a society of different habits. This brought some questions about knowledge of themes in health that students acquire at school or influenced by their culture. The Objective of this research was the influence of scholar teach and the culture arab-muslim into the learning of healthcare from students from three schools of the triple frontier. It is a research with two topics being one of them the documental analysis and the other of descriptive quantitative character that were executed in three schools of arab-muslim teach, being, two schools situated in the city of Foz do Iguaçu and one school in Ciudad Del Este. The documental analysis was constituted by the survey of materials like: Political Pedagogic Project of schools; Teaching plans for teachers; Laws of Guideline and bases of education; National Curricular Parameters; Law 1264 of Education; Paraguai Report and the Educational Programs of MEC from Paraguai. Later on was applied an structured closed questionary between 37 students of third year of High School. For the data analysis was applied a descriptic statistics using the SPPS software. In relation to the educational guidelines, it was realized that the National Curricular parameters controverse themes in health and suggest points that guide the teacher to organize these contents of Teaching Plan. On the other educational programs of Paraguai they contemplate their contents themes in health that must be taught necessarily by the teacher. On this study it was realized that there was influence of social life and religious discipline in points refered to health, in which, scholars through their answers demonstrate have acquired knowledge of themes, like healthy eating and personal hygiene. The best scores were observed in discipline science/biology in themes of drug prevention, contraceptive methods, veneral disease and immunological system. Comparing the three schools, the students of school B had the least scores according with the acquired knowledge of disciplines. It was also realized how the muslim practice healthy habits daily influenced by religion, as it occurs, for example, in practice of hygiene to accomplish prayer and lecture of Qur’an, interviewed students they did not know the practice of ablution like a form of preventing diseases since this practice was routine. It was observed low scores attributed by students in the context of social life themes reffered to preventing diseases like tetanus, tuberculosis, leprosy and dengue, this demonstrate that there must be a better attention to this community for the awareness of educational programs by the health team.